Goal Orientation and Safety Climate: Enhancing Versus Compensatory Mechanisms for Safety Compliance?. (August 2015) - Drach-Zahavy, Anat; Somech, Anit
The study developed and tested a cross-level model for predicting individual differences in nurses' safety compliance, integrating individual-level differences in goal orientation, unit-level safety climate, and their cross-level interactions. Three hundred nurses from 76 units completed validated questionnaires on goal orientation and safety climate; data on safety compliance were obtained through structured observations on nurses administering medications. Results showed that learning goal orientation and avoid performance goal orientation were significantly and positively associated with safety compliance. Cross-level interactions existed between an individual's goal orientation and safety climate and his or her safety compliance: A learning goal orientation was positively related to safety compliance only when safety climate was high, thereby exhibiting an enhancing mechanism. By comparison, an individual's prove performance goal orientation was positively related to safety compliance only when safety climate was low, thereby exhibiting a compensating mechanism. These findings carry important insights for research on person-in-situation models.